Can smartphone use affect chronic disease self-management among Chinese middle-aged and older adults? A moderated mediation model - Gong, Fangmin; Lei, Zhaowen; Min, Hewei; Yu, Yebo; Huang, Zhen; Liu, Jingyao; Wu, Wenyu; Tang, Jingqi; Sun, Xinying; Wu, Yibo (Frontiers in Psychology, 2022)
Introduction Chronic disease self-management is influenced by many factors. Previous studies have linked patients’ media use with chronic disease self-management, but the underlying mechanisms of this relationship are less understood. Objectives The purpose of this study is to explore the mediating role of family health (FH) between frequency of smartphone use (FOSU) and self-management behaviors among middle-aged and older patients with chronic diseases (SBAMAOPWCD) through a moderated mediation model, and whether this indirect relationship is modified by the solitary status of middle-aged and older Chinese patients with chronic disease. Methods Surveys were collected from 1,424 (N = 1,424; age > 45) middle-aged and older with one or more chronic conditions in China on self-reports of FOSU, FH and Chronic disease self-management behaviors were used to examine the moderated mediation model. Results The results showed that the FOSU was significantly and positively associated with SBAMAOPWCD (β = 0.220, p < 0.001; β = 0.170, p < 0.001; β = 0.167, p < 0.001; β = 0.158, p < 0.001); The Family health resources (FHR) dimension of FH and the Family external social supports (FESS) dimension mediated the relationship between the FOSU and SBAMAOPWCD (β = −0.0758, CI: −0.1402, −0.0236; β = 0.0721, CI: 0.0141, 0.1458), Among them, the FHR dimension mediated mainly among FOSU, exercise and cognitive symptom management practices (CSMP; β = −0.0344, CI: −0.0652, −0.0102; β = −0.0401, CI: −0.0725, −0.0138), the FESS dimension of the FH mediated the relationship between the FOSU and communication with physicians (CWP; β = 0.0376, CI: 0.0116, 0.0705); Solitary state played a moderating role in the relationship between FHR dimension and SBAMAOPWCD (live alone β = −0.2395, CI: −0.4574, −0.0661; not live-alone β = −0.0599, CI: −0.1164, −0.0172). In addition, solitary state played a moderating role in the relationship among FHR dimension and CSMP for middle-aged and older patients (live alone β = −0.1095, CI: −0.1961, −0.0378; not live-alone β = −0.0334, CI: −0.0633, −0.0102). Interestingly, the relationship between FESS dimension and SBAMAOPWCD was moderated only by the non-live alone population (β = 0.0676, CI: 0.0008, 0.1478), and not by the live-alone population (β = 0.1026, CI: −0.1061, 0.3278).Unexpectedly, we found that when their FHR were lower, they reported higher levels of chronic disease self-management, middle-aged and older patients with chronic diseases who live alone are more significant in this impact relationship. Conclusions The study further deepens our understanding of the mechanisms linking frequency of smartphone use with chronic disease self-management behaviors, and it helps to develop interventions to improve chronic disease self-management behaviors in middle-aged and older adults.